The Influence of Moisture Content on the Time-Dependent Characteristics of Rock Material and Its Application to the Construction of a Tunnel Portal. (30th September 2015) - Liu, Xiaojun; Yang, Chao; Yu, Jing
Abstract : Uniaxial compression creep experiments were carried out for low-grade metamorphic slate samples (located in the southeastern area of Guizhou province, China) with different moisture contents, using an Instron electric-fluid servo-compression machine. Based on the experimental results, a detailed analysis was made of the effect of moisture content on the strength and deformation behaviour of the slate specimens. The three-parameter generalised Kelvin model was identified to describe the creep behaviour of the low-grade metamorphic slate with different moisture contents. There is an approximately linear negative correlation between the elastic modulus and the saturation degree, and the viscoelastic modulus and viscosity coefficient show a negative exponent correlation with the saturation degree. The Kelvin creep model considering the moisture degradation effect was established and a three-dimensional finite difference model was developed with the software FLAC 3D to validate the creep model. A three-dimensional numerical analysis was then performed to simulate the tunnel excavation process. The results show that the influence of moisture and creep of the surrounding rocks is needed for estimating the deformation of complex tunnel portals.